ARTIFICIAL INTELLIGENCE-BASED LEARNING: COMBINING HUMAN-BASED LEARNING WITH MACHINE INTELLIGENCE - Zulfiya Khabirova (Modern American Journals, 2025)
The rapid development of artificial intelligence (AI) has significant implications for education. AI technologies offer the potential for improved customization, efficiency, and analytics; however, they also provoke ethical dilemmas and challenge traditional pedagogical roles. This study explores the successful integration of human-based pedagogy with AI-based technologies to establish a balanced, human-centered approach to learning. This study examines the theoretical foundations, methodological techniques, and actual implementations to formulate a framework called TEACH-AI (Technologies for Ethical, Adaptive, Complementary, Human-Centered AI). The study’s findings show that AI improves customization, feedback, and formative assessment, while teachers are essential for social-emotional learning, moral reasoning, and contextual judgment. The study suggests that the future of education is based on symbiotic collaboration between humans and intelligent technologies that enhance rather than replace each other.
Keywords: Artificial intelligence, pedagogy, blended learning, teacher practice, intelligent tutoring systems, educational technology, customization, and human-AI collaboration are all important words.